1995
DOI: 10.1016/0275-5408(95)00089-v
|View full text |Cite
|
Sign up to set email alerts
|

Ocular dysfunction associated with mental handicap

Abstract: The aim of this article is to show the main general and ocular characteristics of a group of 46 mentally handicapped people of different IQ and age who were provided with visual care. Many different syndromes and neurological alterations have been described in the literature. The case types and number of people studied for each condition attending our clinics were: syndromes: Down's (25), Soto (2), West (2), Rubinstein-Taybi (1), triple X (1); neurological conditions: cerebral palsy (8), microcephaly (5), hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…Castañe et al . studied the type of refractive error and found that among 46 mentally challenged children, 58.7% had hyperopia (58.7%), 21.7% had myopia (21.7%), and 19.5% had astigmatism, indicating the significantly high proportion of refractive error in these subjects 14. All the aforementioned studies were carried out on mentally challenged children of 5–16 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Castañe et al . studied the type of refractive error and found that among 46 mentally challenged children, 58.7% had hyperopia (58.7%), 21.7% had myopia (21.7%), and 19.5% had astigmatism, indicating the significantly high proportion of refractive error in these subjects 14. All the aforementioned studies were carried out on mentally challenged children of 5–16 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Wong and Ho (1997) evaluated 140 Chinese children in Hong Kong with detailed opthalmologic examination, da Cunha and Moreira (1996) examined 152 children in Brasil, Berk et al (1996) examined 55 patients in Turkey, Castane et al (1995) saw 25 patients in Spain, Roizen et al (1994) evaluated 77 children in Chicago, Courage et al (1994) tested 51 children in Canada, Hestnes et al (1991) saw 30 patients in an institution for individuals with learning diffi culties in Norway and Caputo et al (1989) evaluated 187 medical records in New Jersey.…”
Section: Introductionmentioning
confidence: 99%
“…Non-cycloplegic retinoscopy has been used previously to examine neurologically intpaircd children (Castane et al 1995, Lcat 1996, and enables any significant refnctive error to bc corrected prior to visual icuity assessment. Visual acuity was estimated using both acuity cards and VEE Full details of these procedures have been described previously (Mackie et al 1995).…”
mentioning
confidence: 99%